Thursday

April 17, 2014

April 17, 2014

Posted by **katrina** on Wednesday, June 20, 2007 at 7:58am.

(y-1)/(x +2) = 1/3. Change to

y - 1 = x/3 + 2/3

(y + 3)/(3x -1) = 5/2 Change to

y + 3 = 15x/2 -5/2

4 = 45 x/6 - 2x/6 -15/6 -4/6

43x/6 = 43/6

x = 1

y -1 = 1/3 + 2/3 = 1

y=2

**Related Questions**

derivative - 41) Find the derivative. h(x)= (3x^2 + 1)^3 / (x^2 - 1)^4 This is ...

algebra - (2x+3)/5 = -(3x-2)/2 - (-3/2)(-3/2) I've done this problem a few times...

Derivative Calculus - I just need my answers checked. 1) Find the derivative. f(...

MAth!PLease Help! - 5. Find the x and y intercepts of each linear equation. Be ...

Math - Find the points of inflection of the graph of the function. (If an answer...

math - Find a polynomial f(x) with leading coefficient 1 and having the given ...

calculus - I am trying to find equation of the tangent line to the curve 2/(1-3x...

bobpursley,math - about this problem , I figured it out and i did get the answer...

math - f(x)=-x^3+3x^2+9x-5 asked to find the stationary points this was my ...

algebra help please - The area of a rectangle of length x is given by 3x^2+5x ...